Usborne AI for beginners - Firth, Rachel; Hall, Rose (Usborne Publishing Limited, 2025)
Artificial Intelligence is all about humans asking computers and other machines to think and even behave like humans, and to take on jobs that people find too difficult or too boring. But how do you actually define the term? What exactly can machines with AI already do, and what might they be able to do in the future?AI For Beginners answers all the questions - where answers exist - and raises debating points at every turn about what it all means. Should we be asking machines to do creative tasks, such as writing and illustrating books? Do we need to worry if intelligent machines need to be treated like people? Is there a chance that machines might take over the world, either by accident or on purpose? Is there any point going to school and doing homework if computers can do it all for us, and better?Chapters in this book include:- What is artificial intelligence?- How far has AI come?- How will the world change?How does AI work?AI only exists thanks to computeres. Find out the basics about what computers are and how they work - before diving into the coding secrets that explain how people can teach computers... too teach themselves. AI in actionFind out how AI is being used in everything from searching the internet to solving crimes, looking after people and even waging war. Perhaps most interesting of all, AI tools have given computers the power to talk to people and even create art in ways that feel more and more human. Find out how these tools work, how smart they can be and their limits, too. How AI is changing our worldAs AI-powered machines take on more and more tasks, the way people live is changing. It's not just about what jobs people do - or don't do - anymore. It's about how we make friends and share ideas, and learn about the world. AI might even have the power to solve the climate crisis - or, perhaps, make it worse. Into the futureSome experts are trying to create machines that are just like people. But how similar to a human can a computer program actually be? How much closer might AI ever comt to being.. a 'living' thing?What next?